A Gut Gone to Pot: A Case of Cannabinoid Hyperemesis Syndrome due to K2, a Synthetic Cannabinoid. (29th April 2014) - Ukaigwe, Anene; Karmacharya, Paras; Donato, Anthony
Abstract : Cannabinoid Hyperemesis Syndrome (CHS) was first described in 2004. Due to its novelty, CHS is often unrecognized by clinicians leading to expensive workup of these patients with cyclical symptoms. It may take up to 9 years to diagnose CHS. CHS is characterized by cyclical nausea and vomiting, abdominal pain, and an unusual compulsion to take hot showers in the presence of chronic use of cannabinoids. Cannabicyclohexanol is a synthetic cannabinoid, popularly known as K2 spice. It is a popular marijuana alternative among teenagers and young adults since it is readily available as herbal incense. Unlike marijuana, many users know that K2 is not detected in conventional urine drug screens, allowing those users to conceal their intake from typical detection methods. Serum or urine gas chromatography mass spectrophotometry is diagnostic, though not widely available. Thus, it is imperative for clinicians to recognize CHS, even with negative UDS, to provide cost-effective care. We present a 38-year-old man with a 10-year history of cannabis, and 1-year history of K2 abuse admitted with 1-week history of episodes of nausea, vomiting of clear fluids, and epigastric discomfort. Symptoms are relieved only by hot showers. Extensive laboratory, radiologic, and endoscopic evaluation was unrevealing. CHS was diagnosed, based on proposed criteria by Simonetti et al.